Performance Study and Formulation Optimization of Rapid-Curing Local Insulating Spray Coating Materials - Chengzhi Wang; Long Yang; Xiao Ning; Junchao Xiao; Li Tang; Xueping Xie; Qi Lu (Advances in Polymer Technology)
With the increasing incidence of bird damage affecting the reliability of transmission lines, addressing bird pest control has become an important task for the operation and maintenance of transmission lines. A viable solution involves the application of spray-coated polyurea elastomer composite materials to insulate exposed conductive points and weakly insulated connection parts of transmission line towers. To improve the comprehensive performance of polyurea elastomers, in this study, a polyurea curing system was modified by incorporating aluminum oxide (Al2O3), silicon dioxide (SiO2), and (boron nitride) BN nanoparticles. An orthogonal experiment was designed to investigate the influence of different fillers on the comprehensive performance of polyurea elastomers. These nanoparticles partially filled the defects inherent in the polyurea and BN microparticles, improving the alternating current (AC) breakdown strength of these elastomers. Compared with filler-free polyurea elastomers, optimal performance of the polyurea elastomers was achieved when using 5 wt% Al2O3, 0.4 wt% SiO2, and 5 wt% BN, resulting in a 15.75% increase in the AC breakdown strength and a 10.00% enhancement in the thermal conductivity.